The middle construction in minimalist syntax - Lenardič, Jakob (ELOPE (Ljubljana), 2018)
The paper discusses the argument structure of the English middle construction and its Slovenian equivalent from the perspective of minimalist syntax. The paper first introduces Bruening's (2012) recent approach to syntactic middle formation, which posits that middle sentences are derived via an operator that existentially quantifies over the open agent variable introduced by an active voice projection. Subsequently, the paper argues that the adverbial modifier in the middle construction is not a semantic argument of the null operator, contra Bruening (2012). Finally, the paper proposes that the reflexive morpheme se in the related Slovenian se-sentences plays a role of valency reduction similar to that of the null English operator.
Keywords: argumentna struktura; minimalistična skladnja; povratni morfem; srednjiška zgradba; vezljivost